Nasab Anak dalam Hukum Islam; Membaca Peluang Sains dan Teknologi dalam Penetapan Nasab - Moh. Dliya'ul Chaq (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2018)
The diversity of opinions about childbirth, especially children resulting from illegitimate relationships (zina), interfaith marriages, marriages that are not registered so that their children are not legally recognized in Indonesia seems to cause practitioners of Islamic law (Indonesia) to still not determine an agreement about the status of the child in the problem. In addition, there is still no courage to use science and technology as one of the mechanisms in determining language. Based on this, the focus of the study of this article is to try to read and explore the opportunities for using science and technology in determining how a child is born into a marriage bond. By using in-depth literature data analyzed content, it can be concluded that science and technology have the opportunity as a medium to determine the language of a child, especially for children born in marital and child ties resulting from marriage under hand